A novel missense variant of FBN1 gene in a Sardinian family with Marfan syndrome: a case report - Marsan, Marina; Brutti, Mattia; Meloni, F.; Marica, M.; Soddu, C.; Lai, F.; Martorana, D.; Savasta, S. (Frontiers in Pediatrics, 2025)
BackgroundMarfan Syndrome (MS) is a connective tissue disorder, an autosomal dominant condition mostly caused by variants in the FBN1 gene, which encodes for fibrillin-1 protein. Anomalies in the gene lead to a wide variety of clinical manifestations, including disorders of the cardiac, ocular and musculoskeletal system. We present a case of a child belonging to a Sardinian family of four generations, with a novel variant found in the FBN1 gene.ObjectiveTo include this novel missense FBN1 variant into genetic counselling for Marfan Syndrome and to discuss its genotypic-phenotypic correlation.MethodsFirstly, the proband was diagnosed with Marfan Syndrome using 2020 Revised Ghent Criteria, and she then underwent genetic testing using Next Generation sequencing.ResultsThe NGS revealed a novel heterozygous missense variant (c.2348A>G) in the FBN1 gene, in exon 20. This genetic variant caused a missense substitution of a serine residue with an arginine residue in the position 783 of Fibrillin-1 protein. The variant was then evaluated in the other family members, and was eventually only found in symptomatic individuals, regardless of the severity of their phenotype, demonstrating the segregation with MS; furthermore, it showed complete penetrance with the disease.ConclusionsOur results suggest that this variant is responsible for MS and it therefore should be included in genetic diagnoses and counselling discussion.